2001
DOI: 10.1242/jcs.114.23.4307
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a molecular complex consisting of Fyb/SLAP, SLP-76, Nck, VASP and WASP that links the actin cytoskeleton to Fcγ receptor signalling during phagocytosis

Abstract: Phagocytosis by macrophages and neutrophils involves the spatial and temporal reorganisation of the actin-based cytoskeleton at sites of particle ingestion. Local polymerisation of actin filaments supports the protrusion of pseudopodia that eventually engulf the particle. Here we have investigated in detail the cytoskeletal events initiated upon engagement of Fc receptors in macrophages. Ena/vasodilator-stimulated phosphoprotein (VASP) proteins were recruited to phagosomes forming around opsonised particles in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 179 publications
(28 citation statements)
references
References 69 publications
0
25
1
Order By: Relevance
“…Lpd is central to the regulation of cytoskeletal dynamics 33 as it interacts with multiple actin regulators such as the Ena/VASP family proteins 32,36,65 and the SCAR/WAVE regulatory complex 36,60 . Ena/VASP proteins localize to the phagocytic cup and are indispensable for phagocytosis: Coppolino et al 43 reported that upon binding of Ena/VASP to a cytosolic GFP-ActA construct, phagocytosis was inhibited. In the current study, we were able to validate these findings using a more thorough method that entailed mistargeting Ena/VASP proteins to the mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…Lpd is central to the regulation of cytoskeletal dynamics 33 as it interacts with multiple actin regulators such as the Ena/VASP family proteins 32,36,65 and the SCAR/WAVE regulatory complex 36,60 . Ena/VASP proteins localize to the phagocytic cup and are indispensable for phagocytosis: Coppolino et al 43 reported that upon binding of Ena/VASP to a cytosolic GFP-ActA construct, phagocytosis was inhibited. In the current study, we were able to validate these findings using a more thorough method that entailed mistargeting Ena/VASP proteins to the mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…Interaction between Nck and the T cell receptor (TCR) stimulates PAKdependent actin polymerization, which is important for the formation of the immunological synapse (31,32), and mice deficient in both Nck1 and Nck2 show reduced thymic selection and reduced TCR sensitivity (33,34). Similarly, Nck modulates actin remodeling during phagocytosis in neutrophils and macrophages (35). Work from our group shows an important role for Nck in mediating endothelial activation (27); however, the mechanisms of action appear to be independent of actin remodeling responses.…”
Section: Discussionmentioning
confidence: 99%
“…The processive actin polymerase VASP (vasodilator-stimulated phosphoprotein) is an important regulator of the organization of the actin cytoskeleton. VASP and its homologues, Mena and Evl, are involved in the formation of lamellipodia and filopodia, , as well as the cellular processes of phagocytosis, cell migration, ,, and neuron axon guidance . VASP functions both as an actin polymerase and as an anti-capping protein, ,, by protecting the barbed end of actin filaments from capping proteins.…”
mentioning
confidence: 99%